Effect of CAD–CAM Framework Design Fabricated from Sintered Cobalt–Chromium Alloy on Fracture Resistance of Metal–Ceramic Restorations - Kourosh Afshar; Mehran Falahchai; Homeira Ansarilari; Gelareh Tajziehchi (International Journal of Dentistry)
Introduction. Porcelain fracture is a common problem of metal–ceramic restorations (MCRs). One suggested strategy to prevent it is to modify the metal framework design; however, the available information regarding the effect of framework design on porcelain fracture is scarce. Objective. This study aimed to assess the effect of computer-aided design and computer-aided manufacturing (CAD–CAM) framework design fabricated from sintered cobalt–chromium (Co–Cr) alloy on fracture resistance of MCRs. Materials and Methods. Twenty premolar metal dies were fabricated for this in vitro study. Ten standard frameworks were designed with 0.5 mm thickness, and 10 customized frameworks were designed with 1 mm thickness at the lingual margin and 0.5 mm thickness in all other areas. All specimens were fabricated from sintered Co–Cr alloy (Ceramill Sintron) using soft metal milling technology. After porcelain application, the specimens underwent thermocycling and cyclic loading for 3,000 cycles between 5 and 55°C. The fracture resistance was measured by a universal testing machine. The failure mode was also determined. Data were statistically analyzed by independent t-test (α = 0.05). Results. The mean fracture resistance of porcelain was 2,379 ± 531 N in the standard and 2,557 ± 448 N in the customized group. No significant difference was found in fracture resistance of the two groups (P>0.05). All specimens in both groups showed mixed failure. Conclusion. The fracture resistance of porcelain and the failure mode were not affected by the framework design of MCRs fabricated from sintered Co–Cr alloy (Ceramill Sintron).